African coups in the COVID-19 era: A current history - Chin, John J.; Kirkpatrick, Jessica (Frontiers in Political Science, 2023)
What explains the explosion of coup activity in Africa over the last few years? To answer this question, this article presents narrative summaries – a current history – of all eleven coups attempts in Africa between August 2020 and November 2022. We then discuss the most relevant causal explanations for the observed increase in coup frequency in Africa in this period. Though we find relatively little evidence of direct coup diffusion or democratic backsliding as coup triggers, our findings suggest that coup-struck African countries over the last few years are disproportionately poor, have a recent history of coups, and face ongoing dilemmas of democratic consolidation. Ongoing Islamist insurgencies may have helped precipitate recent coups in West Africa but not elsewhere.